Instagram Content Analysis for Effectiveness Information Delivery - Gunawan, Doni; Prasetia, Andreas (oneamrd (One a Mllions Dreams Corporation), 2024)
This study aims to analyze the effectiveness of information delivery through Instagram content of the Mojokerto City Education and Culture Office. The research method used is content analysis with a qualitative approach through data condensation, data presentation and drawing conclusions. Data were collected through direct observation of the official Instagram account of the office, as well as interviews with account managers. The results of the study indicate that although the content presented is quite informative, there are several weaknesses in terms of posting consistency, content variation, and interaction with followers. Data analysis also revealed that the level of community engagement is still low, which is caused by the lack of interactive strategies and optimal use of Instagram features. This study suggests improving content planning, using Instagram features more effectively, and increasing interaction with the community to improve the effectiveness of information delivery. Thus, it is hoped that the Mojokerto City Education and Culture Office can be more effective in delivering information and building better relationships with the community.